Development and validation of food frequency questionnaire for urban hemodialysis population in selected dialysis centres at the Klang Valley, Malaysia - Md Ali, Mohammad Syafiq (2020)
Dietary assessment among hemodialysis population plays a crucial role in evaluating the quality of patients’ dietary intake. Adequate dietary intake will prevent malnutrition thus decrease the mortality rate among the population. A rapid and reliable tool that can be appropriately applied to quantify macronutrients and micronutrients consumed by Malaysian hemodialysis population is lacking. Therefore, the aim of this study is to develop and validate a food frequency questionnaire (FFQ) applicable to assess dietary intake for urban hemodialysis population in Malaysia. This study was divided into three phases: Phase I was the development of the FFQ whilst Phase II and Phase III provided for the validation of the FFQ. In Phase I, three days dietary recall (3DDR) from 388 subjects in the ‘Nutrition Status and Lifestyle Assessment in Hemodialysis Population, Malaysia’ study was selected based on inclusion criteria, and were used to construct a food item list using the Block’s method. A food nutrient database was then built inclusive of macro- and micronutrients. In Phase II, face validation (n=10) and content validation (n=10) were carried out. The final FFQ consisted of 123 food items. In Phase III, relative validation was then carried out with 121 subjects selected through consecutive sampling method [Malay=64%, Chinese=23% and Indian=13%; female=45%, male=55%; mean age=53±12 years; blood pressure=155/83, Malnutrition Inflammation Score ≥ 6 (Malnourished=24%)]. Anthropometry, biochemical profiles and dietary assessment for these subjects were assessed. The face validation of the FFQ indicated most food groups were well understood by lay persons and nutrition experts with the exception for ‘cooked rice’ groups (p<0.05). Mean time to complete the FFQ was 42±5 minutes. The mean difference for absolute intakes of total energy, carbohydrate, protein, total fat, sodium, potassium, phosphate, calcium and iron assessed by 3DDR and FFQ were significant (p<0.01). There was a significant correlation between FFQ and 3DDR assessments when comparing absolute intakes for total energy, carbohydrate, protein, total fat, sodium, potassium, phosphate, calcium and iron with correlations ranging from 0.35-0.47 (p<0.01). Cross-quartile classification indicated 70% to 82% subjects were classified into same or adjacent quartiles and 3.3% to 7.4% subjects were grossly misclassified when comparing absolute intakes assessed by FFQ and 3DDR. Bland-Altman plots showed more than 90% of subjects were scattered within the limit of agreement for all the nutrients between FFQ and 3DDR. This FFQ was developed appropriate to assess dietary intake of urban Malaysian hemodialysis population. The FFQ is suitable to be applied in nutritional epidemiological studies to assess populations’ diets contribute to malnutrition or any other health conditions.